Struktur Modal Dalam Perusahaan Syariah Di Indonesia - Nurul kholisha; Laeni Khazimah; Sri Mumaeni Agustina; Sabina Sukma Maulidya; Gunawan Aji (CV. KAMPUSA AKADEMIK PUBLISING, 2024)
When choosing the capital structure of a company, you must be careful, because this decision can affect the cost of capital and capital budgeting decisions. An optimal capital structure can maximize company value and improve service quality. In this context, this research aims to reveal the capital structure used in sharia companies in Indonesia. This research will use descriptive research methods. Collecting information from literature sources and secondary data. The capital structure of sharia companies in Indonesia is still in the development stage. Sharia companies need to continue to innovate and find solutions to overcome existing challenges, such as: lack of various sharia capital instruments, sharia regulatory requirements, low public literacy about sharia capital instruments. The government and sharia regulators also need to play an active role in supporting the development of sharia capital structures in Indonesia. With joint efforts from various parties, it is hoped that the sharia capital structure in Indonesia can develop more rapidly and contribute to the progress of the sharia economy. Keywords: Capital Structure, Sharia Companies, Capital